Analisis Faktor-Faktor yang Memengaruhi Continuous Intention to Use Aplikasi Mobile Game Online di Indonesia - Zaid Al Fatiy; Diena Noviarini; Sabo Hermawan (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to analyze the partial effects of hedonic motivation, habit, and social influence on the continuous intention to use mobile game online applications in Indonesia. This research employs a quantitative approach using a survey method and Structural Equation Modeling based on Partial Least Squares (SEM-PLS) as the data analysis technique. The sample consists of 192 users of mobile game online applications in Indonesia selected through purposive sampling. The data were analyzed using SmartPLS software. The results indicate that: (1) hedonic motivation has a positive and significant effect on the continuous intention to use mobile game online applications; (2) habit has a positive and significant effect on the continuous intention to use mobile game online applications; and (3) social influence has a positive and significant effect on the continuous intention to use mobile game online applications. These findings emphasize the importance of enhancing the quality of gaming experience, fostering positive usage habits, and optimizing social interaction within applications to increase users’ intention to continue using mobile game online services